If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9f + 5(-8 + 3f) = 0 9f + (-8 * 5 + 3f * 5) = 0 9f + (-40 + 15f) = 0 Reorder the terms: -40 + 9f + 15f = 0 Combine like terms: 9f + 15f = 24f -40 + 24f = 0 Solving -40 + 24f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 24f = 0 + 40 Combine like terms: -40 + 40 = 0 0 + 24f = 0 + 40 24f = 0 + 40 Combine like terms: 0 + 40 = 40 24f = 40 Divide each side by '24'. f = 1.666666667 Simplifying f = 1.666666667
| 2[t-(2t+18)+15]=2(t+3) | | 4x+235=12x-5 | | (k,k+14)=0 | | 7y+8=1 | | 4m=12 | | 0.65x+.05(8-x)=.10(76) | | -28p-6(3-6p)=6(p-4)-2 | | 400x-100(30-x)=0 | | 8x^2-7x+4=-3x+2 | | 3x+41-6x=2-9x+3 | | t+23=15 | | 48(b+12)=63+56b | | x+.40=4 | | =3(2y+4)7-30 | | 2x-3(1-3x)=10 | | 4t^3-27t^2+60t-45=0 | | 10u-98=3u | | -9(v+2)+3v+7=8v+7 | | 10-98=3u | | -5z=11-6z | | 4x^2-9x-33=0 | | x^2+3x+8=-4x-2 | | 7-4x=3l | | 105=(2x-11) | | M+18=36 | | x^2-x+4=6 | | 7x(6+9x)-2x(8+5x)= | | h=300+3.5h | | -5=c/4/3 | | -3d+7=1-5d | | 4t^3-9t^2+60t-45=0 | | (x+8)+4=x+(8+4) |